M= (x+5)² - (x-5)² + 3 + 20x

N=(a+3)² –(a-3)²
-10a




e= (x+2)²-(x-2)²-8x




a= (2a+b)²-(2a-b)²

2(2ab)




b=(x+3)²-(x-3)²

c= (x+3)²+(x-3)²
D= (a+1)²+(a-1)²
E= (a+1)²-(a-1)²
F=(x+5)²+(x-5)²
g= (3x+2)²-(3x-2)²
H= (x³+3)²+(x³-3)²
i= (x/2+1)²-(x/2-1)²

1

Respuestas

2013-06-27T04:08:05+02:00
M=x^2+10x+25-x²+10x-25+3+20x=40x+3
N=a²+6a+9-a²+6a-9-10a=12a-10a=2a
b=x²+6x+9-x²+6x-9=12x
c=x²+6x+9+x²-6x+9=2x²+18
d=a²+2a+1+a²-2a+1=2a²+2
e=a²+2a+1-a²+2a-1=4a
f=2x2+50
g=9x²+12x+4-9x²+12x-4=24x
h=x⁶+6x³+9+x⁶-6x³+9=2x⁶+18








que esta elevado al cuadrado es decir a la dos
gracias suerte que te vaya bien en todo bye
a=(4a²+4ab+b²)-(4a²-4ab+b²)/4ab=(4a²+4ab+b²-a²+4ab-b²)/4ab=4ab/4ab=1
De nada.
GRACIASSSSS